Predictors for symptom re-exacerbation after targeted stepwise drug discontinuation in first-episode schizophrenia: results of the first-episode study within the German research network on schizophrenia - Gaebel, Wolfgang; Schmitt, Andrea (Schizophrenia research, 2016)
Background: After a first episode in schizophrenia guidelines recommend antipsychotic maintenance treatment (MT) for at least 1year. Recent RCTs on subsequent targeted intermittent treatment (IT) after stepwise drug discontinuation yielded noticeably higher relapse rates than during MT also in first-episode patients. Nevertheless, about 50% of patients remain stable under IT. Given the potential adverse effects of antipsychotics and the preference of many patients to discontinue drugs, valid predictors for the feasibility of IT are urgently needed to support decision making. Methods: Based on a one-year RCT phase comparing MT with IT in first-episode patients after 1year of MT, conducted within the German Research Network on Schizophrenia (GRNS), predictors for deterioration under IT in 19 feasible patients were identified by logistic regression analysis. Results: Deterioration occurred in 10 patients (52.6%). Univariate analyses indicated a lower PANSS positive score after acute treatment as well as after one year of MT as significant predictors; in multivariate logistic regression, in addition to the lower PANSS positive score after acute treatment, reaching enduring remission and having had a deterioration both during MT evolved as significant predictors and indicate a higher risk for deterioration. Conclusions: Although limited by the small sample size, our findings suggest that patients who show a favorable response and full and enduring symptom remission during antipsychotic treatment, as well as those with marked deterioration despite MT should rather be recommended to remain on treatment because they are at higher risk for symptom re-exacerbation after (stepwise) drug discontinuation.